Thermoeconomic optimization of a LiBr absorption refrigeration system - Kızılkan, Önder; Sencan, Arzu; Kalogirou, Soteris A. (My University, 2007)
Optimization of thermal systems is generally based on thermodynamic analysis. Thermoeconomic optimization technique combines thermodynamic analysis with economic constraints to obtain an optimum configuration of a thermal system. In this study, the thermoeconomic optimization technique is applied to a LiBr absorption refrigeration system. Various components of the system such as condenser, evaporator, generator, and absorber heat exchangers are optimized. Additionally, optimum heat exchanger areas with corresponding optimum operating temperatures are determined. A cost function is specified for the optimum conditions. Finally, an example for the optimum design of a 20 kW LiBr system is given.
Keywords: Thermoeconomic optimization; Absorption refrigeration; Heat exchangers; Refrigeration